Nutritional Status and Body Composition in Wilson Disease: A Cross-Sectional Study From China - Geng, Hao; Wang, Shijing; Jin, Yan; Cheng, Nan; Song, Bin; Shu, Shan; Li, Bo; Han, Yongsheng; Han, Yongzhu; Gao, Lishen; Ding, Zenghui; Xu, Yang; et al. (Frontiers in Nutrition, 2021)
Background: Abnormal nutritional status is frequently seen in patients with chronic diseases. To date, no study has investigated the detailed characteristics of abnormal nutritional status among Wilson disease (WD) patients in the Chinese cohort. This study aimed to describe the nutritional status of WD patients, with a particular focus on the differences between patients with different phenotypes. Methods: The study subjects comprised 119 healthy controls, 129 inpatients (hepatic subtype, n = 34; neurological subtype, n = 95) who were being treated at the affiliated hospital of the Institute of Neurology, Anhui University of Chinese Medicine. All of the subjects were assessed for body composition by using bioelectrical impedance analysis. All WD patients received anthropometry, nutritional risk screening 2002 (NRS2002), and laboratory test (hemocyte and serum biomarkers) additionally. Results: Compared with healthy controls, the fat mass and rate of total body and trunk were significantly higher in WD patients (P<0.001), the muscle and skeletal muscle mass of total body and trunk were significantly lower in WD patients(P<0.001). Compared with hepatic subtype patients, the fat mass and rate of total body, trunk, and limbs were significantly lower in neurological subtype patients (P<0.01); while there were no significant differences in muscle and skeletal muscle between these two subtypes. The overall prevalence of abnormal nutritional status in WD patients was 43.41% (56/129). The prevalence of high-nutritional risk and overweight in WD patients was 17.83% (23 of 129) and 25.58% (33 of 129), respectively. Compare with patients with high nutritional risk, macro platelet ratio, alkaline phosphatase, the basal metabolic rate (p<0.05), creatinine, trunk fat rate (p<0.01) and appendicular skeletal muscle mass (p<0.001) were significantly higher in patients without nutritional risk (p<0.001). Patients with a high nutritional risk tend to have a lower cholinesterase concentration (x2=4.227, p<0.05). Conclusion: Both patients with H-subtype and N-subtype are prone to have an abnormal nutritional status. Longitudinal studies are required to investigate if nutritional status and body composition could reflect prognosis in WD patients, and which of these body composition indexes contribute to malnutrition and worse prognosis.